2021
DOI: 10.1177/2284026520984366
|View full text |Cite
|
Sign up to set email alerts
|

That one doctor. . . Qualitative thematic analysis of 49 women’s written accounts of their endometriosis diagnosis

Abstract: Introduction: One in nine women experience endometriosis, a common gynaecological disease, yet time to diagnosis averages 7 years. People are sharing their endometriosis experiences online. This research’s aim was to expose and synthesise the collective themes of diagnostic experience. Method: A qualitative thematic analysis of publicly accessible online autobiographical accounts of women and their endometriosis diagnosis. Themes were coded within NVIVO and thematic maps and tables created. Eighty-nine origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The meta-synthesis also noted the positive experiences reported when women were transferred quickly to specialist care (ibid). Fernley’s (2021) analysis of online public accounts in Australia of experiences leading to endometriosis diagnosis produced some themes similar to Pettersson and Berterös (2020) meta-synthesis; it also reported how a significant majority of women remained unaware of endometriosis for some time. Rowe et al (2021) further recommends longer-term care planning and a collaborative approach to care incorporating women’s self-knowledge and expertise.…”
Section: Introductionmentioning
confidence: 89%
“…The meta-synthesis also noted the positive experiences reported when women were transferred quickly to specialist care (ibid). Fernley’s (2021) analysis of online public accounts in Australia of experiences leading to endometriosis diagnosis produced some themes similar to Pettersson and Berterös (2020) meta-synthesis; it also reported how a significant majority of women remained unaware of endometriosis for some time. Rowe et al (2021) further recommends longer-term care planning and a collaborative approach to care incorporating women’s self-knowledge and expertise.…”
Section: Introductionmentioning
confidence: 89%
“…There are several patient characteristics that impact speed of endometriosis diagnosis including age, ethnicity, and knowledge about endometriosis [24][25][26][27][28]. Furthermore, the normalization of pain, the internalized stigma surrounding women's health, and the capacity to selfadvocate are also important contributors [18,25,[28][29][30][31][32][33][34][35][36].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Age is an additional barrier to diagnosis [25,26]. Younger patients report having their HCPs insist that they are too young to present with endometriosis [25] although symptoms appear in some individuals shortly after first menstruation [27]. An international survey found that some individuals experienced the symptom onset of endometriosis at age 16 or younger [37].…”
Section: Social Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health blogging – writing blogs about health conditions – is also relatively common. Academic research has explored the blogging activities of women with breast cancer (Martino et al, 2019; McNamara, 2007), burns survivors (Garbett et al, 2017), women with endometriosis (Fernley, 2021), people with depression (Kotliar, 2016), as well as health blogging more generally (see, for example, Rains & Keating, 2011). Health blogging has been examined as a means of providing social support for people with health conditions (Rains & Keating, 2011), and has been associated with modest improvements in wellbeing (Rains & Keating, 2015), and there is a suggestion that reading blogs written by someone with personal experience of a health condition (in this case HIV) are more persuasive in changing action than blogs written by professionals (Neubaum & Krämer, 2015).…”
Section: Introductionmentioning
confidence: 99%